Effect of an Asthma Guideline in 2 Pediatric Emergency Departments and an Urgent Care Center. Issue 10 (October 2018) - Dilts, Jennifer J.; Humiston, Sharon G.; Lee, Brian R.; Allen, Nancy H.; Michael, Jeffrey G.
Abstract : Objectives: The objective of this study was to evaluate ordering of albuterol via metered-dose inhaler with spacer (MDI-spacer), length of stay (LOS), and 72-hour return rates before and after publication of an internally developed pediatric asthma clinical practice guideline (CPG). Methods: The internally developed CPG reflected national recommendations. It was explained at faculty meetings by a respected clinician and published on the intranet on February 6, 2012. We performed a retrospective study of visits from January 1, 2009, to October 31, 2014, by children aged 2 to 17 years with a primary diagnosis of asthma and discharged from a target site (2 pediatric emergency departments and 1 urgent care center). We excluded critical/emergent visits and those by patients who transferred to the emergency department/urgent care center from another facility or were admitted. We extracted data for 37 months before and 33 months after CPG implementation (post-CPG) using a single electronic health record system. Results: Albuterol delivery via MDI-spacer increased by 33.95% ( P < 0.0001) during 1-month post-CPG implementation with no significant subsequent decrease. An unexpected decline was noted for median LOS before CPG implementation (−1.24 minutes; P < 0.0001). For MDI-spacer–treated patients post-CPG, decreased median LOS was maintained and there was decreased variability of the median LOS ( P < 0.001). For nebulizer-treated patients post-CPG, median LOS increased (.95 minutes; P = 0.033). No change was observed for 72-hour return rates. Conclusions: Implementation of an asthma CPG increased ordering of albuterol via MDI-spacer. The increase was sustained over time in all study sites. Decreased variability in median LOS for MDI-spacer patients was observed post-CPG. Median LOS for those treated with MDI-spacer exclusively remained unchanged in the post-CPG period, whereas post-CPG LOS increased in those who received nebulized albuterol.